2020
DOI: 10.1101/2020.04.27.20075085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How urgent do intravitreal anti-VEGF injections need to be to justify the risk of transmitting COVID-19? Proof-of-concept calculations to determine the Health Adjusted Life-Year (HALY) trade-off

Abstract: and KEY WORDS

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“… 27 In a study comparing the risk of COVID-19 infection and transmission among neovascular AMD patients with visual impairment caused by the neovascular AMD, Boyd et al reported that reduced disease burden from avoiding visual impairment outweighs the expected health-adjusted life-years lost from COVID-19 transmission. 28 For CRVO, the long-term follow-up in the HORIZON trial previously showed that a delay in follow-up resulted in worsening of the visual acuity in CRVO but not in BRVO patients, in concordance with our sub-group analysis. 29 As diabetic macular edema represents the most common indication for intravitreal injection in our cohort, and the most common cause of vision loss from diabetic retinopathy, 30 we further sub-analyzed diabetic macular edema patients.…”
Section: Discussionsupporting
confidence: 89%
“… 27 In a study comparing the risk of COVID-19 infection and transmission among neovascular AMD patients with visual impairment caused by the neovascular AMD, Boyd et al reported that reduced disease burden from avoiding visual impairment outweighs the expected health-adjusted life-years lost from COVID-19 transmission. 28 For CRVO, the long-term follow-up in the HORIZON trial previously showed that a delay in follow-up resulted in worsening of the visual acuity in CRVO but not in BRVO patients, in concordance with our sub-group analysis. 29 As diabetic macular edema represents the most common indication for intravitreal injection in our cohort, and the most common cause of vision loss from diabetic retinopathy, 30 we further sub-analyzed diabetic macular edema patients.…”
Section: Discussionsupporting
confidence: 89%